Modeling and optimizing of nonlinear electromagnetic processes. Non-synchronous interaction of free electrons with the electromagnetic radiation field - A. A. Kurayev; V. V. Matveyenka (Doklady Belorusskogo gosudarstvennogo universiteta informatiki i radioèlektroniki)
The main results of the researches in the scientific direction «Modeling and optimizing nonlinear electromagnetic processes» for 2013-2018 years are presented. On the basis of numerical simulation, the effect of systematic (independent of the frequency and phase of the field) braking and reflection of an ensemble of free electrons, initially moving in the direction of an elementary electric radiator, is established. One of the practical applications of the found effect in a terahertz generator with asynchronous interaction, the spherotron, is shown. The role of the established effect in the processes of asynchronous interaction of free electrons with the field of electromagnetic radiation in the ionosphere and the solar corona is indicated.